Theoretical nuclear physics - Blatt, John M.; Weisskopf Victor F (New York: Dover Punlications Inc., 1979)
An uncommonly clear and cogent investigation and correlation of key aspects of theoretical nuclear physics by leading experts: the nucleus, nuclear forces, nuclear spectroscopy, two-, three- and four-body problems, nuclear reactions, beta-decay and nuclear shell structure. Directed to the experimental physicist working in nuclear physics or graduate students who know the essential concepts and problems. 112 illustrations.
Appendix A-B, 781-815p.;Bibliographical references 817-847p.;Index 849-864p.
Keywords: Nuclear physics; Nuclear reactions; Nuclear spectroscopy; Theoretical physics